STUDY OF THE MOTIVATION OF THE PROFESSIONAL ACTIVITIES OF TEACHERS IN THE CONDITIONS OF WAR IN UKRAINE - Олексенко, Світлана; Хоменко, Олена (Modern engineering and innovative technologies, 2024)
Motivation is an important element in progressive development during the professional activity of a teacher. During the period of martial law in Ukraine, teachers continue their professional activities, which require further improvement of professional sk